Prescrito e o vivido: estudo da política de ampliação da jornada escolar em escolas de tempo integral da rede municipal de educação de Goiânia - Gomes, Marcilene Pelegrine (2016)
This thesis is linked to the line research State, Policies and History of Education of the Program of Post-graduation in Education of the Faculty of Education of the Federal University of Goiás (PPGE/FE/UFG). The study object is the extended school time policy in the Full Time Schools (EMTI) of the Municipal Secretary of Education of Goiânia (SME). The general objective is to investigate the effectiveness of this policy by the analysis of the financial, administrative and pedagogical capacity of the educational system to guarantee the material and human conditions for the quality of the teaching and learning process in Full Time Schools. This is a case study carried out with the first five (05) schools that implemented the EMTI in the Municipal Education System in 2015. The procedures used in this research were documental, bibliographic and field research. The main analyses consisted on the following areas: the financing, the school infrastructure, the development of the teaching process and the school management conditions. Based on quantitative and qualitative and objective and subjective data, the investigation is epistemologically supported by the studies of Amaral (2012), Brasil (2006, 2009a, 2010a, 2010b), Carreira and Pinto (2007), Dourado, Santos and Oliveira (2007), Dourado and Oliveira (2009), Fineduca (2013) Oliveira and Araújo (2005), Oliveira (2007), Pinto (2014, 2015), Souza, Gouveia and Scheneider (2011), Scheneider (2012) and Barra et al. (2015). In the development of the exhibition registers, through data and analysis, in municipal policy falls within the set of policies for basic education in Brazil implemented over the last two decades with centrality in the expansion of the school day in order to ensure improvement in student academic performance and, at the same time, offer a full-time care for children in situations of social vulnerability. It is stated as a thesis that material and human conditions, objective and subjective, municipal policy implementation in the five in outline stresses and contradictions present in municipal law, in speeches and in everyday school officials who, in turn, show limits, challenges and possibilities for the effectiveness of the proposal on RME de Goiânia as State public policy.